THE SPECIFICS OF VALUE ORIENTATIONS OF THE NATIVE PEOPLES OF THE NORTH - Maryam A. Ryabova (Вестник Кемеровского государственного университета, 2016)
The paper presents and discusses the results of the 2013 – 2014 survey of a number of students from native peoples of the North and non-indigenous students living in Magadan. The survey allowed, firstly, to compare the features of valuable orientations of students among the native peoples of the North and non-indigenous students; secondly, to determine the specifics of valuable orientations of students among the indigenous people. To examine the specificity of students from the native peoples of the North and non-indigenous students M. Rokeach’s method of “valuable orientations” was used. It was found that the surveyed samples of indigenous peoples and non-indigenous peoples have similar structure of the terminal and instrumental values: among value-goals, the first position is taken by “health” and “happy family life”, among values-means – “education” and “educatedness”, but the students originating form indigenous people value the beauty of nature and art higher. Thus, these data show that the understanding of significant life values of students from indigenous and non-indigenous people is very similar and does not depend on their ethnic group.